Exploring Speech Acts and Common Ground in Student Corruption Discourse: Insights from Southeastern Universities in Nigeria - Kenneth Obinna Patrick; Amarachi Stephenie Osondu (PT FORMOSA CENDEKIA GLOBAL, 2026)
Using the mixed method research design, the study looks at how students use speech acts and shared knowledge to negotiate meanings around morally and legally questionable behaviours, drawing on Speech Act Theory and Common Ground Theory. The study's examination of focus groups, participant interviews, and naturally occurring conversations shows that corruption is frequently spread covertly through code-switching and uniquely grounded expressions that mainly rely on mutual understanding among peers. These pragmatic strategies assist to preserve group cohesion and steer clear of overt moral judgment in addition to reflecting underlying sociocultural attitudes regarding corruption. The study contributes to how language both reflects and reinforces institutional and pervasive corruption in higher educational institutions by revealing the influence of context, purpose, and common knowledge on corruption-related discourse.